Table of Cotents - Table of Contents, Table of Contents (Advances in Nursing & Midwifery, 2019)
Evaluation of the Clinical Performance of Nurses Employed in the Neonatal Intensive Care Units.........1 Fateme Amiri Simkoii, Anahita Masoumpoor, Azam Shirinabadi-Farahani, Bagher Pahlevanzadeh The Effect of Reproductive Factors on Coronary Artery Disease in Women..............................................9 Soodabeh Darvish, Saeed Sadeghian, Azizeh Ghaseminejad, Reza Mohebi The Study of Nurses Knowledge and Performance Quality of Qazvin Hospitals about the Process of Blood Transfusion.......................................................................................................................................14 Fatemeh Nemati, Amirhosein Maali, Mohammad Hossein Ahmadi, Hoda Poorkarim, Hanieh Rahmani, Zahra Sadat Tabatabaei, Mehdi Azad The Effect of Employment of Nursing Students on their Academic Achievement in the School of Nursing and Midwifery of Shahid Beheshti University of Medical Sciences.............................................19 Feryal Esnaashari, Tahereh Fathi Najafi, Nasrin Razmkhah, Mehri Ardakani The Evaluation of Functional Quality in Bachelor Midwifery Students based on Objective Structured Clinical Examination (OSCE) in Islamic Azad University-Mashhad Branch...........................................23 Hajar Beirami, Hadi Rezghi Shirsavar Prediction of Mental Health in MS Patients: The Role of Psychological Resilience and Cognitive Integration...................................................................................................................................................29 Maryam Kazemi Correlation between Spiritual Leadership and Occupational Conflict.....................................................33 Masoumeh Namdar, Mansoureh Zagheri Tafreshi, Foroozan Atashzadeh-Shoorideh, Maliheh Nasiri Relationship between Spiritual Experiences and Organizational Commitment with Perceived Stress at the staff of Tehran Oil Hospital..................................................................................................................39 Mohammad Reza Yavari, Soraya Zarrini Application of Photovoice in Qualitative Researches................................................................................46 Alireza Nikbakht Nasrabadi, Fatemeh Najafi, Leila Mardanian-Dehkordi